C-type natriuretic peptide attenuates enhanced glycolysis and de novo pyrimidine synthesis in pericytes of patients with pulmonary arterial hypertension - Minhee Noh; Ankita Mitra; Lisa Krebes; Werner Schmitz; Jan Dudek; Stuti Agarwal; Christoph Maack; Paula Arias-Loza; Takahiro Higuchi; Ivan Aleksic; Vinicio A. de Jesus Perez; Michaela Kuhn; et al. (Communications Biology)
Abstract Metabolic reprogramming of vascular cells plays a crucial role in Pulmonary Arterial Hypertension (PAH), marked by a shift from oxidative phosphorylation to glycolysis (Warburg effect), altered purine biosynthesis, impaired glutaminolysis and fatty acid oxidation, driving endothelial and smooth muscle cell hyperproliferation. The metabolic alterations underlying pericyte dysfunction in PAH remain largely unexplored. Here, we investigated the metabolic alterations in PAH lung pericytes and the impact of C-type natriuretic peptide (CNP) and Guanylyl Cyclase-B/cyclic GMP signaling on these changes. Our results demonstrate that PAH pericytes exhibit increased glucose uptake, glycolysis, and de novo pyrimidine synthesis, promoting their hyperproliferation. These changes are driven by the upregulated glucose transporter, GLUT-1 and Pyruvate dehydrogenase kinase 1, along with enhanced CAD (Carbamoyl-phosphate synthetase 2, Aspartate transcarbamoylase, and Dihydroorotase) activity, both in vitro and in situ. CNP counteracts these alterations through activation of cGMP-dependent kinase I, reducing HIF-1α and GLUT-1 expression and thereby glucose uptake. Additionally, CNP activates Phosphodiesterase 2 A and thereby inhibits CAD activation and de novo pyrimidine synthesis. Accordingly, CNP prevented growth factor-induced proliferation and metabolic changes in murine pericytes within precision-cut lung slices. This study highlights dysregulated metabolic pathways in PAH pericytes and the therapeutic potential of CNP.